Factors affecting consumers' cognition of food photos using Kansei engineering - WU,Mei-Yi (2022)
Abstract The charm of food photos plays a decisive role in advertising because people search and buy food on the Internet more frequently than ever. Photos with appealing food design elements can immediately attract people's attention. The same food with different design features will attract different consumer groups through photos on the web. They greatly affected consumers' feel, and purchase decisions. This study uses Taiwanese mango ice as an example to explore the perceptual reasons why consumers are attracted to existing mango ice products, their attractive design features, and the relationship between the two. Miryoku engineering was used to explore the relationship between consumers and the appeal of food design revealed by photos, the Evaluation Grid Method (EGM) was used to extract the attractive factors of food design, and the Quantification Theory Type 1 (QTT1) is used to analyze the weight of each design feature that affects the charm of food. Three Kansei factors and 16 concrete design elements were obtained through EGM, and the weights of food design elements that influence the charm were found using QTT1. The results show that the obtained regression models can explain the relationship between the design elements of food photos and the perception of customers. The application have important reference value for evaluating food design elements and market segmentation of consumer groups. This research proves the feasibility of using Kansei engineering to explore the charm of food design, and has reference value for future related research.